Hubungan peran Keluarga dengan Perilaku Seks Pranikah Pada Remaja SMP Negeri 5 Ungaran - Umi Setyoningrum; Liyanovitasari Liyanovitasari (Indonesian Journal of Nursing Research (IJNR), 2019)
Pre-marital sexual behavior in adolescents is increasing and has a negative impact on the development and growth of adolescents. This was influenced by several factors including the role of families that did not function optimally. If in a family, the teenagers get less attention, then they will act recklessly because they feel there is no prohibition from parents. There is no form of advice, prohibition or punishment if a mistake is made, this proves the lack of attention of parents to adolescents. Low supervision ofadolescent activities will have an impact on adolescents’ behavior. This study aims to determine the correlation between family roles and premarital sexual behavior in junior high school students. This research was cross sectional designand it was carried out by measuring and observing variables at the same time. The number of samples as many as 185 participants were taken by purposive proportional random sampling technique. This study found that there is correlation between family roles and premarital sexual behavior in adolescents with p value 0.029. parents role are needed in adolescent relationship with peer and guide them to choose good friends.Keywords :The Role of Family, Premarital Sexual Behavior in Adolescents